HEALTH EDUCATION INTERVENTION: EFFECTIVENESS OF FIRST AID TRAINING IN AN EARLY CHILDHOOD EDUCATION TEAM - Pereira dos Santos, Bianca; Maria Mariano Costa, Claudiele; Bonadio Gonçalves, Fabio; Rodrigues Leite, Giovana; Lourenço de Almeida, Caroline; Cristina Ferrarezi Barboza, Danielle (Health and Society, 2023)
The project is based on the importance of first aid in the school context. When thinking about traumas, deaths and sequelae related to children, falls, burns, drowning and suffocation are highlighted. Health promotion and prevention in schools is aimed at the various accidents to which children are vulnerable. With effective first aid, it is possible to perform adequate early intervention and reduce injuries and sequelae, thus reducing the patient’s suffering. Faced with accidents, teachers may have difficulties in making the right approach, hence the strategy of training them through simulations. Train employees of early childhood education in the identification and early intervention in the face of accidents within the institution; conduct an interview, assess their knowledge, carry out realistic interventions and simulations in first aid in different scenarios. This is a quasi-experimental, before-and-after, analytical study with a quantitative and qualitative approach to data treatment and analysis, with a view to evaluating realistic simulation as a teaching strategy in the acquisition of knowledge in first aid in children for teachers of the kindergarten. The work provided experiences of teaching and learning content related to the practice of first aid. It was a unique moment, in which, even in the face of the difficulty of time available for the researches, it was possible to establish a collaborative work between them and the researchers. In absolute numbers, there was a slight improvement in the post-test. Understanding the importance of the problem worked on, it is suggested that the training be carried out in a greater number of meetings, allowing for greater reflection, training, experiences and learning.